THE WORLD OF TAx DEDUCTIONS - Alexei V. Dujov (Статистика и экономика, 2016)
In this article a study and methodological foundations of the structure of taxes and fees. Disclosed the concept of elements of tax and duty. Focuses on the nature of the concept of «tax deduction». Provides legal and the author’s interpretation of the term «tax deduction». Examples of application of a tax deduction in the value-added tax and the tax to incomes of physical persons. the conclusions about the multilateral nature of the tax deduction.